PENDAYAGUNAAN LIMBAH CAIR TAHU SEBAGAI PUPUK ORGANIK CAIR DI DESA KUNCEN - Oktavianus Cahya Anggara; Rifky Firmansyah Ramadani; Alfa Wahyu Fharentha; Ranti Sofia Mega Putri; Ismi Nur Setyaningtyas; Chintia Khoirun Nisa; Ninda Nur Faiqoh (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Liquid organic fertilizer derived from liquid tofu waste is an example of converting waste into valuable resources. The process of making liquid organic fertilizer from liquid tofu waste involves the fermentation of microorganisms that break down the organic materials in the waste. The result of this fermentation is a nutrient-rich solution containing beneficial microbes for plants. The fermentation process takes 15 days to become liquid organic fertilizer, with the addition of EM4 (Effective Microorganisms 4), a solution of brown sugar, and sufficient water. Utilizing liquid tofu waste to create liquid organic fertilizer can help mitigate the negative environmental impacts of improperly disposed liquid waste. By transforming waste into useful fertilizer, it can contribute to establishing a more sustainable and eco-friendly agricultural system. This activity involves the tofu industry located in the Kuncen village of Padangan sub-district, as well as members of the Community Service Program for Students (KKN-TK) from Group 13 at Bojonegoro University.